Acute low back pain as infusion-related reaction to monoclonal antibodies - Majenka, Pawel; Loquai, Carmen; Schöning, Tilman; Enk, Alexander; Hassel, Jessica (Frontiers in Oncology, 2023)
Monoclonal antibodies, such as PD-1 inhibitors, are increasingly used in various cancers. Acute low back pain as infusion-related reaction (IRR) to monoclonal antibodies is poorly described. We report a bicentric series of 10 cases of acute low back pain due to administration of monoclonal antibodies directed against PD-1/PD-L1 for skin cancer treatment in patients treated at University Hospital Heidelberg and University Medical Center Mainz (Germany). The management of IRR symptoms was immediate interruption of infusion and analgesia leading to quick improvement and complete symptom relief in all patients. Our findings suggest that the risk of developing low back pain as IRR is depending on the concentration of the administered drug. Low back pain as IRR can be managed by early interruption of infusion and by decreasing the infusion rate or concentration in following administrations.